Social Media Phenomena with Negative Contents - Chontina Siahaan; Laras Nadiananda Iswari; Nova Betriani Sinambela (International Journal Labs, 2021)
Social media is very trending used among teenagers to communicate. The information contained is not only in a positive form but is conveyed also in negative forms such as sexual harassment. The study's problem is to find out why teens are sexually harassed through social media. The purpose of this study was to find out the forms of sexual abuse committed by adolescents and how to overcome them. Research methods are qualitatively descriptive with critical paradigms. The informant of this study is a teenagers as perpetrators and victims of sexual abuse. Data were collected through Focus Group Discussion (FGD). The results of this study suggest that sexual harassment is highly likely to occur in public spaces, specifically through social media. Perpetrators are very easy to publish negative information with the aim of arousing martyrdom. Such information is like teasing the victim both in the comments field, sending negative images, and making video calls by showing physical forms that lead to pornographic elements. The occurrence of sexual harassment through social media certainly has an impact on high levels of fear and anxiety for victims. The recommendation in this study is that it is necessary to educate teenagers as the next generation of the nation to be smart in using social media with positive content.